2013
DOI: 10.1063/1.4793223
|View full text |Cite
|
Sign up to set email alerts
|

Differential electronic detector to monitor apoptosis using dielectrophoresis-induced translation of flowing cells (dielectrophoresis cytometry)

Abstract: The instrument described here is an all-electronic dielectrophoresis (DEP) cytometer sensitive to changes in polarizability of single cells. The important novel feature of this work is the differential electrode array that allows independent detection and actuation of single cells within a short section ([Formula: see text]) of the microfluidic channel. DEP actuation modifies the altitude of the cells flowing between two altitude detection sites in proportion to cell polarizability; changes in altitude smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Larger cells and cells passing closer to the electrodes produce larger signals. 27 The two peaks form the detection signature for each cell. When a DEP voltage is applied, the cells will be attracted or repelled from the higher density electric field region; meaning depending on the magnitude and sign of the Claussius Mossotti factor the second peak will be larger or smaller than the first peak.…”
Section: B Dep Cytometermentioning
confidence: 99%
See 1 more Smart Citation
“…Larger cells and cells passing closer to the electrodes produce larger signals. 27 The two peaks form the detection signature for each cell. When a DEP voltage is applied, the cells will be attracted or repelled from the higher density electric field region; meaning depending on the magnitude and sign of the Claussius Mossotti factor the second peak will be larger or smaller than the first peak.…”
Section: B Dep Cytometermentioning
confidence: 99%
“…The DEP cytometer is based on differential detection of single cells before and after DEP actuation in a microfluidic channel and has been described in detail by Nikolic-Jaric et al 27 Briefly, the cell first passes over a first pair of detection electrodes, Fig. 3(c), and produces a signal with a peak value of P 1 .…”
Section: B Dep Cytometermentioning
confidence: 99%
“…Fig. 10 shows the simulated spectrum of RefK CM g for a CHO cell with parameters given in Table II and medium conductivity of 0.01 and 0.17 S/m (close to medium conductivities used in several pervious works 10,39,43,59,[62][63][64] ). It demonstrates that changing the radius of the nucleus by 25% (while keeping all other parameters the same) causes a noticeable change in the spectrum for medium conductivity 0.17 S/m.…”
Section: E Cho Double-shell Model Parametersmentioning
confidence: 99%
“…Discrepancies between dye exclusion and electrical properties based viability assays have been reported and analyzed by other groups as well, where the electrical technique based viability decreases at a faster rate than the dye exclusion test based viability. 38,39 The rapid decrease in cell viability measured by our technique, relative to the dye exclusion test, suggests that the detected changes in the cell polarization response capture the transition to a suboptimal physiological state occurring during the initial stages of cell death. NS0 cells, analyzed by us in this study, have been previously reported to be susceptible to their environment and their apoptosis can be triggered relatively easily compared to other industrial cell lines.…”
mentioning
confidence: 99%